Olfactory misinformation: creating "fake news" to reduce problem foraging by wildlife. Issue 9 (21st June 2022) - Price, Catherine; McArthur, Clare; Norbury, Grant; Banks, Peter
Abstract : Finding food is a key motivator of animal behavior and underpins an increasing number of conservation and wildlife management challenges. Introduced predators threaten many vulnerable native species, and some native predators are problematic for declining prey species. Likewise, browsing by native and introduced herbivores threatens endangered plant species, undermines habitat restoration efforts, and alters plant communities. Mammalian predators and herbivores use olfactory information to forage efficiently, pursuing cues that are useful and ignoring those that are not. Here, we present the theoretical basis for why olfactory misinformation should alter foraging decisions and provide compelling evidence that supports the theory. Drawing on this theory and evidence of the success of olfactory misinformation where it has been applied to date, we propose that there is enormous scope for its application more broadly in conservation and wildlife management. Such an approach offers a robust behavioral alternative for protecting valued plants and prey species that are otherwise vulnerable to foraging mammals.